Perception, diagnosis and management of BK polyomavirus replication and disease in paediatric kidney transplant recipients in Europe - Pape, Lars; Tönshoff, Burkhard; Hirsch, Hans H. (Nephrology, dialysis, transplantation, 2016)
Abstract Background. BK polyomavirus (BKPyV)-associated nephropathy remains a challenge to the success of kidney transplantation, but its impact varies in diffe
Published: 20 November 2015
Gesehen am 18.09.2019